Residential Schools Locations Project
This dataverse contains datasets associated with the Residential Schools Locations Project. This datasets in this project show the precise locations of the Residential Schools (Boarding Schools, Industrial Schools and Hostels) in Nova Scotia, Quebec, Ontario, Manitoba, Saskatchewan, Alberta, British Columbia, Yukon Territory, Northwest Territories and Nunavut. Data was created by Rosa Orlandini with significant contributions from the National Centre for Truth and Reconciliation, and minor contributions from Morgan Hite and Stephanie Pyne.
Keywords: _open access

The Canadian Peoples 1871-1921 census data
The Canadian Peoples (TCP) data infrastructure encompasses 40 million coded and georeferenced census records from 1852-1921 including personal, family and household characteristics for every individual in each enumeration. The Canadian Foundation for Innovation, provincial research funds in Quebec, Ontario and Alberta, nine Canadian universities and Ancestry.com have funded the project. The owner of these data, Ancestry.com, has agreed to license their use for academic research and educational purposes only, with no right to publish, transfer, share, sub-license or distribute any portion of the data. Access to data for research and educational purposes may occur upon approval of a completed application by the TCP approvals committee. Any research institution or research seeking access to any of the data within this collection will need to complete the application form and send it to the TCP project director Kris Inwood at: kinwood@uoguelph.ca The first census year for distribution is 1871; the data for other years will follow as soon as they can be made ready.
Keywords: _open access

Les gens de Paris, 1926-1936
Recherche dans les listes nominatives de recensement de population des années 1926, 1931 et 1936 à Paris.
Keywords: _open access

Canada Census Search - Library and Archives Canada
Application Description
Last Modified: Date modified (YYYY-MM-DD) / Date de modification (AAAA-MM-JJ)
Keywords: _open access